Toward the sun: a preface to taner Murat's The sounds of tatar spoken in Romania - Kevin Marshall Chopson (Историческая этнология, 2017)
This article explores the specific value of Taner Murat’s work in his new book The Sounds of Tatar Spoken in Romania and the value of linguistics, translation, and cultural preservation in general. Part book review, personal memoir, political and social commentary, philosophy, and poetry, it is a partial exploration of the beauty of language and the power of words. The article proposes the importance of “difference” as opposed to the widespread homogenization of cultures due to the proliferation of internet usage, democracy, capitalism, and efficiency. Sources cited include Joseph Joubert, Darrin McMahon, Mark C. Taylor, Peter Gay, and Ludwig Wittgenstein. One theme explores the effects of the over-unification of cultural ideas and state systems under the broader influence of larger powers, corporate or political, based on the American model or other hallmarks of contemporary Western Civilization.